The Effect Of Teaching Vocabulary by Using Flashcard for Seventh Grade Students at Mts Sa Darul Istiqomah Kepohbaru - Iin Widya Lestari; Astrid Chandra Sari; Fatimatuz Zahro (STAI Miftahul Ula Nganjuk, 2018)
Vocabulary is the basic language aspect that should be mastered before mastering English skills, but most of seventh grade students in MTs SA Darul Istiqomah Kepohbaru still had lack of vocabularies. Therefore the researcher used flashcard as an effort in improving students’ vocabulary mastery. The reason drive the researcher to conduct a research that is the effect of teaching vocabulary by using flashcard for seventh grade students in MTs SA Darul Istiqomah Kepohbaru. The research method used in this study was a quasi-experimental research. The samples were class 7.3 as experimental class and class 7.4 as control class. The collected data in this research were analyzed by using t-test. The result of data analysis showed, the t-value was 33,928 with degree of freedom 23 in the significant level 5% and the t-table was 1,7138. It meant that t-value was higher than t-table. Therefore, the null hypothesis (Hₒ) was rejected and alternative hypothesis (Hₐ) was accepted. There was significant difference between students’ vocabulary achievement by using flashcards and without flashcards. Thus, it could be concluded that the teaching vocabulary using flashcards was effective on improving students’ vocabulary mastery.